Yu.A. Zeleneev – Researcher of the Volga Region Medieval Archaeology - Alexander A. Vybornov; Vladimir V. Stavitsky (Археология евразийских степей, 2023)
The authors describe the main directions of the research work of one of the leading specialists in the Volga region’s medieval archaeology – Yu.A. Zeleneyev, who celebrates his 70th anniversary on July 9, 2023. Authors of article share their memoirs and impressions about the meetings with him, tell about the main marks of his creative way. A. Zeleneyev started to be involved in archaeology in the Mordovia State University, after graduating he began his postgraduate study under the guidance of G.A. Fyodorov-Davydov at the Mordovia Research Institute. After finishing postgraduate study, he got a job at the Mordovia University and in 1984 moved to Yoshkar-Ola, where he works in Mari State University until now. A. Zeleneyev's scientific interests are connected with the medieval archaeology and history of Volga region. Up to the beginning of the 1990s the burial rite of medieval Mordva in the VI–XI centuries was his main research theme, then he gradually passed to the study of the ethnic and cultural history of the Volga region in the Golden Horde period. Firstly he carried out the excavations on the Narovchat fortified settlement, after he began systematic studies of the Selitrennoye settlement. The results of studies were summarized in his doctoral dissertation, which materials were published in a monograph that was highly appreciated by the scientific community. Since 2019 the results of the Selitrennoye ancient settlement excavations have been publishing in the form of monographic editions.